El virus del rayado fino del maíz: estudios adicionales sobre la relación del virus y su insecto vector - Paniagua, R; Gámez, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The leafhopper Dalbulus maidis was able to acquire maize rayado fino vids (MREV] after a 6 b feeding period on diseased plants, and transmit it lo healthy plants after inoculation feedings of 8 hb. Slightly higher proportions of viruliferous insects we obtained with prolonged acquisition 05 inoculation feeding periods Colonies of 23 10 40 per cent hansmiters in the TP. generation were developed though controlled mattings and selection of virliferons progeny, ubile 17 10 28 per cent rectors were obtained from non-viruliferous progeny. The more active colonies retuvred to a level of 11 10 28 per cent vectors following a feic generations of random mating In the more active colony 75 per cent of the females were viviliferons as compared 10 43 pe cent of the males. Puncturing the anterior abdomen of nymphs inmediately before or after acquisition, increased slightly the ability of D. maidis to hansmit MREV. A number of species of Giaminae and Cyperacede appeared not susceptible 10 the virus and mese poor hosts for D maidis. MREV was nit transmiled by the plamtboppei Peregrinus maidis.